2003
DOI: 10.1016/s1607-551x(09)70432-2
|View full text |Cite
|
Sign up to set email alerts
|

Kikuchi‐Fujimoto Disease: A Case Report

Abstract: We describe a rare but typical case of Kikuchi-Fujimoto disease (KFD). Two subcutaneous nodules appeared suddenly on the right of the neck of a 15-year-old girl. Microscopy of a surgical specimen of the larger nodule showed necrotizing lymphadenitis. Prompt treatment with mepirizole resulted in the disappearance of the smaller nodule. No recurrence was noted during 6 months of follow-up. KFD is a rare, self-limiting, necrotizing histiocytic lymphadenitis that needs to be differentiated from malignant lymphoma.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 25 publications
0
4
0
1
Order By: Relevance
“…In many instances, Kikuchi disease is a self-limiting disorder that regresses spontaneously in 1–4 months with symptomatic management with antipyretics and analgesics. Unresponsive cases need to be treated with systemic corticosteroids to aid in early recovery [ 21 ]. Hydroxychloroquine and intravenous immunoglobulins are some of the specific therapeutic options which have been used with successful outcomes [ 22 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…In many instances, Kikuchi disease is a self-limiting disorder that regresses spontaneously in 1–4 months with symptomatic management with antipyretics and analgesics. Unresponsive cases need to be treated with systemic corticosteroids to aid in early recovery [ 21 ]. Hydroxychloroquine and intravenous immunoglobulins are some of the specific therapeutic options which have been used with successful outcomes [ 22 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…suggested that KFD and systemic lupus erythematosus (SLE) have in common a hyperimmune reaction, which later is expressed as two different manifestations: one compromising lymph nodes (KFD), and the other manifesting as SLE. Thus, diagnosing KFD can be challenging given the similarities between KFD-lymphadenopathy and other autoimmune-lymphadenopathies and that KFD is not a well-known entity among clinicians and pathologists 8 , 9 .…”
Section: Discussionmentioning
confidence: 99%
“…A definitive diagnosis of KFD can be made only by histological examination of the affected node; diagnostic imaging studies (chest radiography, ultrasound, CT scanning or MR imaging) confirm the presence of enlarged lymph nodes in the affected areas but cannot specifically confirm a diagnosis of KFD [31]. Node extirpation is appropriate, as the findings of fine needle aspiration are most often nonspecific [5]. Morphologically, the lesion affects the cortical and paracortical areas of the node with single or multiple necrotic foci.…”
Section: Discussionmentioning
confidence: 99%
“…Although its pathogenesis remains unclear, it is assumed that the disease results from a genetic predisposition with a consecutive hyperimmune reaction to various agents or an autoimmune reaction with lymphocyte apoptosis as a key factor [5]. The aim of this report is to increase awareness of the possibility of KFD since this disease can easily be mistaken for lymphoma or systemic lupus erythematosus (SLE) and thus patients might be overtreated.…”
Section: Introductionmentioning
confidence: 99%